A stablecoin that’s actually stable: A portfolio optimization approach - Grobys, Klaus; Junttila, Juha-Pekka; Kolari, James W. (Journal of Financial Stability, 2025)
Stablecoins seek to address the high price fluctuations of unbacked cryptocurrencies, such as Bitcoin and Ether. However, recent studies as well as the collapse of stablecoin USTC (Terra) cast doubt on the stability of stablecoins. Using well-known Markowitz portfolio optimization methods, we combine five leading stablecoins into a global minimum variance portfolio that represents a stable aggregate stablecoin (SAS). We find that SAS is much more stable than its constituent stablecoins. Also, in a stress test adding USTC to the portfolio, SAS remains stable with a narrow price range over time. Importantly, the construction of SAS using modern diversification methods has practical implications for the ongoing development of central bank digital currencies (CBDCs).